Multilocational evaluation of black sigatoka resistance in banana and plantain - Gauhl, F.; Pasberg-Gauhl, C.; Vuylsteke, D.R.; Ortíz, R. (1995)
Black sigatoka is a leaf spot disease on plantain and banana. Its sausal agent is the fungus Mycos-phaerella fijunsis Morelet. Black sigatoka is one of the most important constraints of plantain and banana cultivation throughout the world. Yield loss can be up to 50 %. Chemical control of the disease is possible, but expensive, and the small farmer cannot afford to pay for it. Cultivation of resistant clones is the best control method. However, black sigatoka response can vary for different locations.